Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1210/en.2004-0913
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy Induces Spermatogenesis and Partially Restores Fertility in Luteinizing Hormone Receptor Knockout Mice

Abstract: Testosterone (T) is essential for spermatogenesis, fertility, and maintenance of the male phenotype. We analyzed in hypogonadal LH receptor knockout (LuRKO) male mice whether T treatment can restore their phenotype, spermatogenesis, and fertility. In LuRKO mice, spermatogenesis is arrested at round spermatids, adult-type Leydig cells are absent, T production is dramatically decreased, the animals are cryptorchid, and their accessory sex organs are atrophic. T replacement therapy from 21 d of life for 60 or 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 57 publications
8
77
0
1
Order By: Relevance
“…Recently Pakarainen et al 162 reported that four of six (67%) testosterone-treated LH receptor knockout (LuR-KO) mice exhibited marked inflammation in the prostate, characterized by the abundant presence of lymphocytes in stromal tissue and between tissue layers in prostate glands. The 8 week long testosterone replacement regimen started at the prepubertal age of 21 days to restore both anatomical abnormalities and accessory sex organ function in these hypogonadal LuRKO male mice.…”
Section: Mouse Models Of Prostatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Pakarainen et al 162 reported that four of six (67%) testosterone-treated LH receptor knockout (LuR-KO) mice exhibited marked inflammation in the prostate, characterized by the abundant presence of lymphocytes in stromal tissue and between tissue layers in prostate glands. The 8 week long testosterone replacement regimen started at the prepubertal age of 21 days to restore both anatomical abnormalities and accessory sex organ function in these hypogonadal LuRKO male mice.…”
Section: Mouse Models Of Prostatitismentioning
confidence: 99%
“…[163][164][165] Additionally, in some LuRKO mice testosterone replacement also induced severe inflammation in the coagulating glands, vasa deferentia, and epididymis. 162 Long-term administration of testosterone in Lobund-Wistar and Noble rat strains has been shown to induce invasive prostate adenocarcinomas. 61,166 It has been demonstrated that testosterone alone blocks 17b-estradiol-induced prostate inflammation, but prostatitis has not been reported to occur in animals treated with testosterone alone.…”
Section: Mouse Models Of Prostatitismentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, poorly developed secondary sex characteristics and infertility are observed in both sexes. Further detail about the phenotype of this model are in our previous reports (Zhang et al, 2001a;Zhang et al, 2003;Zhang et al, 2004;Pakarainen et al, 2005c;Pakarainen et al, 2005b;Pakarainen et al, 2005a).…”
Section: Lh/hcg-r Knockout (Lurko) Micementioning
confidence: 99%
“…Ovarian transplantation has been used to investigate the mechanism of reproductive failure in transgenic mice (13,16,17), and ovarian wedge resection is often used very successfully to restore fertility to anovulatory women. In the present study, we have used ovarian transplantation and wedge resection as tools to study subfertility in ER␤ Ϫ/Ϫ mice.…”
mentioning
confidence: 99%